Sarcoma European and Latin American Network (SELNET) Recommendations on Prioritization in Sarcoma Care During the COVID‐19 Pandemic. (23rd September 2020) - Martin‐Broto, Javier; Hindi, Nadia; Aguiar, Samuel; Badilla‐González, Ronald; Castro‐Oliden, Victor; Chacón, Matias; Correa‐Generoso, Raquel; Álava, Enrique; Donati, Davide María; Eriksson, Mikael; Falla‐Jimenez, Martin; German, Gisela; et al.
Abstract: Background: The COVID‐19 outbreak has resulted in collision between patients infected with SARS‐CoV‐2 and those with cancer on different fronts. Patients with cancer have been impacted by deferral, modification, and even cessation of therapy. Adaptive measures to minimize hospital exposure, following the precautionary principle, have been proposed for cancer care during COVID‐19 era. We present here a consensus on prioritizing recommendations across the continuum of sarcoma patient care. Material and Methods: A total of 125 recommendations were proposed in soft‐tissue, bone, and visceral sarcoma care. Recommendations were assigned as higher or lower priority if they cannot or can be postponed at least 2–3 months, respectively. The consensus level for each recommendation was classified as "strongly recommended" (SR) if more than 90% of experts agreed, "recommended" (R) if 75%–90% of experts agreed and "no consensus" (NC) if fewer than 75% agreed. Sarcoma experts from 11 countries within the Sarcoma European‐Latin American Network (SELNET) consortium participated, including countries in the Americas and Europe. The European Society for Medical Oncology‐Magnitude of clinical benefit scale was applied to systemic‐treatment recommendations to support prioritization. Results: There were 80 SRs, 35 Rs, and 10 NCs among the 125 recommendations issued and completed by 31 multidisciplinary sarcoma experts. The consensus was higher among the 75 higher‐priority recommendations (85%, 12%, and 3% for SR, R, and NC, respectively) than in the 50 lower‐priority recommendations (32%, 52%, and 16% for SR, R, and NC, respectively). Conclusion: The consensus on 115 of 125 recommendations indicates a high‐level of convergence among experts. The SELNET consensus provides a tool for sarcoma multidisciplinary treatment committees during the COVID‐19 outbreak. Abstract : The COVID‐19 pandemic has caused deferral, modification, or cessation of treatment for patients with cancer. This article presents a consensus on prioritizing recommendations across the continuum of sarcoma patient care.